Pengaruh Edukasi Kesehatan Menggunakan Media Ular Tangga Terhadap Tingkat Pengetahuan Tentang Hiv/Aids pada Remaja di SMP Budi Utama - Ari Sanjaya Putra, I Gede; Gede Subhaktiyasa, Putu; Ni Nyoman Sintari, Silvia (Pustaka Galeri Mandiri, 2026)
Adolescents often have limited knowledge about HIV/AIDS, lacking understanding about transmission, prevention, and the long-term effects of HIV/AIDS. The main objective of this study was to investigate whether a redesigned snakes and ladders game with an innovative approach could significantly improve adolescents' understanding of HIV/AIDS. This study used a pre-experimental design with a single group pre-test and post-test approach. The sample consisted of 74 ninth-grade students from Budi Utama Junior High School, who were selected through purposive sampling. Data on HIV/AIDS were collected using questionnaires administered before and after the intervention using the snakes and ladders game. Data analysis used the Wilcoxon Signed Rank Test with a significance level of ? = 0.05. Most respondents (66.2%) had a low level of knowledge about HIV/AIDS. After the intervention with the snake and ladder game, most respondents (86.5%) demonstrated a good level of knowledge, as indicated by the Wilcoxon test results, which produced a p-value of 0.000 (p < 0.05), showing a significant positive effect after education using the snake and ladder game medium. Therefore, the use of the snakes and ladders game as an educational method can be an innovative and attractive alternative in health education efforts for adolescents in HIV/AIDS prevention